1982
DOI: 10.1159/000145496
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Vagal Nature and Anatomical Access Paths to Esophagus Laminar Nerve Endings in Myenteric Ganglia. Determination by Surgical Degeneration Methods

Abstract: The dependence, access paths and functional significance of the intraganglionic laminar nerve endings (IGLEs) in the esophageal wall of the cat are demonstrated. To this end Wallerian degeneration was induced on the vagus nerve by a number of surgical operations performed at the nodose ganglion level. The results show IGLEs to be sensorial receptors dependent on neuronal bodies situated in the nodose ganglion. The nerve fibers on which they depend to reach the esophageal wall gain access via the vagus and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 12 publications
2
60
0
Order By: Relevance
“…In addition to IMAs, IGLEs are mechanoreceptors associated with the myenteric ganglia of the cat esophagus (34). IGLEs are not physically associated with ICC (20,29), and, in W/W v mutant mice lacking ICC-IM, IGLEs were not affected (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to IMAs, IGLEs are mechanoreceptors associated with the myenteric ganglia of the cat esophagus (34). IGLEs are not physically associated with ICC (20,29), and, in W/W v mutant mice lacking ICC-IM, IGLEs were not affected (21).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that more than one structurally and functionally distinct type of mechanoreceptor exists within the esophagus (4,5,8). As early as 1929, intraganglionic laminar nerve endings (IGLE) were considered candidates for esophageal stretch receptors (34). In an elegant study by Berthoud and Powley (4), intramuscular vagal afferents were shown to be positioned and structured as likely candidates for the gastric stretch receptor.…”
mentioning
confidence: 99%
“…They present as profuse leafy structures covering myenteric ganglia from the esophagus to the colon. Neurectomy experiments (Rodrigo et al 1982) and anterograde wheat germ agglutinin-horseradish peroxidase (WGA-HRP) tracing from the nodose ganglion (Neuhuber 1987) have identified their vagal afferent nature. Morphological findings of an intimate relationship of IGLEs to connective tissue layers enveloping myenteric ganglia in the rat esophagus (Neuhuber 1987;Neuhuber and Clerc 1990) and electrophysiological studies in the guinea pig indicated that IGLEs function as mechanotransduction sites of vagal tension receptors both in the esophagus (Zagorodnyuk and Brookes 2000;Zagorodnyuk et al 2003) and stomach (Zagorodnyuk et al 2001).…”
mentioning
confidence: 99%
“…Quantification of IGLEs. Criteria for IGLE identification were as determined previously: an IGLE must consist of (1) a laminar aggregate of (2) fine terminal puncta (3) within the neuropil of a myenteric ganglion, and (4) must cover all or part of the myenteric ganglion (Rodrigo et al, 1975(Rodrigo et al, , 1982Neuhuber, 1987;. Counting of IGLEs was conducted at 100ϫ magnification and verified at 200ϫ when necessary.…”
Section: Anterograde Labeling Of Vagal Gi Afferentsmentioning
confidence: 99%
“…Among vagal GI afferents, intraganglionic laminar endings (IGLEs) are the predominant vagal mechanoreceptor innervating GI smooth muscle (SM) and are concentrated in the region of the upper GI tract in which most food collects during consumption of a meal Wang and Powley, 2000). They consist of plates of densely packed terminal puncta that innervate myenteric ganglia and are activated by muscle wall tension or stretch and possibly by satiation hormones, such as CCK (Rodrigo et al, 1982;Schwartz and Moran, 1994;Zagorodnyuk et al, 2001).…”
Section: Introductionmentioning
confidence: 99%